2010
DOI: 10.1258/ijsa.2010.010281
|View full text |Cite
|
Sign up to set email alerts
|

Jarisch–Herxheimer reaction among syphilis patients in Rio de Janeiro, Brazil

Abstract: The Jarisch-Herxheimer reaction (JHR) is a syndrome observed after antimicrobial treatment of some infectious diseases. The syndrome has clinical characteristics of an inflammatory reaction to antibiotic treatment. A prospective study of patients with a clinical and laboratory diagnosis of syphilis was conducted at a sexually transmitted diseases clinic in Rio de Janeiro, Brazil. Patients were treated with benzathine penicillin and observed for the JHR. A total of 115 patients were included in this study. Fift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 10 publications
2
12
0
2
Order By: Relevance
“…Nowadays, the incidence of the JHR varies between 9% and 31% which is in line with the 28% found in our study . However, earlier studies found higher rates around 40–60% up to 95% in primary syphilis .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Nowadays, the incidence of the JHR varies between 9% and 31% which is in line with the 28% found in our study . However, earlier studies found higher rates around 40–60% up to 95% in primary syphilis .…”
Section: Discussionsupporting
confidence: 91%
“…It has also been suggested that the RPR titres could be correlated with a higher bacteremia, but in this study, RPR titres were not related to JHR. The JHR started 6 h after the treatment, in a similar way as that described in previous studies . This reaction is harmless and self‐limited in general.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…For example, 50 to 75% of the patients with primary or secondary syphilis may experience the Jarisch-Herxheimer reaction, which typically occurs within 2 to 5 hours of initiation of penicillin therapy for syphilis and usually resolves within 24 hours [7,13,14]. In the study by Miller et al ., the overall incidence is around 9% in syphilis patients regardless of stage [15]. Patients with HIV infection and pregnant women have a higher incidence of the Jarisch-Herxheimer reaction while receiving syphilis treatment, with a rate of 35 and 40%, respectively [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of constitutional symptoms and absence of dermatophytes by KOH preparation and DPAS stain argues against tinea corporis/cruris. 24 The biggest differences between our patient and those patients with typical JHR are the later time of onset, longer duration of symptoms, and the lesser severity of symptoms, not the type of symptoms (Table 1). 4,5,[20][21][22][23] Despite the onset of new lesions of EM, complete recovery days after antibiotic withdrawal and good health 5 years later negate the possibility of treatment failure and chronic Lyme disease.…”
Section: Discussionmentioning
confidence: 70%